Improved Medicago sativa Nodulation under Stress Assisted by Variovorax sp. Endophytes - Noris J. Flores-Duarte; Julia Pérez-Pérez; Salvadora Navarro-Torre; Enrique Mateos-Naranjo; Susana Redondo-Gómez; Eloísa Pajuelo; Ignacio D. Rodríguez-Llorente (Plants, 2022)
Legumes are the recommended crops to fight against soil degradation and loss of fertility because of their known positive impacts on soils. Our interest is focused on the identification of plant-growth-promoting endophytes inhabiting nodules able to enhance legume growth in poor and/or degraded soils. The ability of Variovorax paradoxus S110T and Variovorax gossypii JM-310T to promote alfalfa growth in nutrient-poor and metal-contaminated estuarine soils was studied. Both strains behaved as nodule endophytes and improved in vitro seed germination and plant growth, as well as nodulation in co-inoculation with Ensifer medicae MA11. Variovorax ameliorated the physiological status of the plant, increased nodulation, chlorophyll and nitrogen content, and the response to stress and metal accumulation in the roots of alfalfa growing in degraded soils with moderate to high levels of contamination. The presence of plant-growth-promoting traits in Variovorax, particularly ACC deaminase activity, could be under the observed in planta effects. Although the couple V. gossypii-MA11 reported a great benefit to plant growth and nodulation, the best result was observed in plants inoculated with the combination of the three bacteria. These results suggest that Variovorax strains could be used as biofertilizers to improve the adaptation of legumes to degraded soils in soil-recovery programs.